Study of the function of Thyroid gland in β- thalassemia major male patients in Kirkuk city. - Mossa M. Marbut; Bassam Saleh Jameel; Amina H. Hamed; Issa H. Kareem (Journal of Madenat Alelem University College, 2016)
Thalassemia has been classified by the world health organization as a major public health problem. It occurs throughout the world and regarded as one of the major health problems in endemic regions as Middle East, Mediterranean countries, Asia and North Africa. Endocrine complications in Thalassaemia Major Patients with multitransfused Thalassaemia Major patients may develop severe endocrine complications. Due to multiple transfusions is the main cause of such complications, Iron accumulates in many tissues such as liver, heart and endocrine glands. The study aims to study the function of Thyroid gland in β- thalassemia Major male patients in Kirkuk city. The study was conducted β-thalassaemia major patients whom attended the thalassaemia center in Azadi Teaching hospital in Kirkuk Governorate from September 2015 to the end of January 2016. A total of 105 male subjects were participated in the study, (30 normal healthy subjects and 75 thalassaemic patients). Body weight height was measured. About, five ml of venous blood were obtained from all normal subjects and patients. One ml of blood sample was collected for measurement of packet cell volume (PCV) and heamoglobin (Hb). The remaining four ml of blood sample were used for serum separation. Serum used for measurement of serum thyroid stimulating hormones (TSH), T3 and T4. Results of study showed a high significant decrease in body weight and height of male thalassemic patients as compare with male counterpart of control subjects of same age. Also, there was a highly significant reduction in the concentration of heamoglobin and PCV value in thalassaemic male patients as compared with control male subjects. There is no significant increase in serum Thyroid stimulating hormone (TSH) concentration in male thalassemic patients as compare with male control subjects. However, there is highly significant reduction in serum T4 and T3 concentrations in male thalassemic patients as compare with male control subjects.